Evaluating the bonding of two adhesive systems to enamel submitted to whitening dentifrices. - Briso, André Luiz Fraga [UNESP]; Toseto, Roberta Mariano; de Arruda, Alex Mendes; Tolentino, Patricia Ramos; de Alexandre, Rodrigo Sversut; Santos, Paulo Henrique dos [UNESP] (My University, 2010)
The aim of this study was to evaluate by micro-shear bond strength test, the bond strength of composite resin restoration to enamel submitted to whitening dentifrices. Forty bovine teeth were embedded in polystyrene resin and polished. The specimens were randomly divided into eight groups (n=5), according to the dentifrice (carbamide peroxide, hydrogen peroxide and conventional dentifrice) and the adhesive system (Prime & Bond 2.1 and Adper Single Bond 2). Dentifrice was applied for 15 minutes a day, for 21 days. Thirty minutes after the last exposure to dentifrice, the samples were submitted to a bonding procedure with the respective adhesive system. After that, four buttons of resin were bonded in each sample using transparent cylindrical molds. After 24 hours, the teeth were submitted to the micro-shear bond strength test and subsequent analysis of the fracture mode. Data were submitted to analysis of variance and Fisher's PLSD test (alpha = 0.05). The micro-shear bond strength showed no difference between adhesives systems but a significant reduction was found between the control and carbamide groups (p = 0.0145) and the control and hydrogen groups (p = 0.0370). The evaluation of the failures modes showed that adhesive failures were predominant. Cohesive failures were predominant in group IV The use of dentifrice with peroxides can decrease bonding strength in enamel.
Keywords: acetone; Adper single bond 2; polymethacrylic acid derivative; prime and bond 2.1; tooth bleaching agent; tooth cement; toothpaste; animal; cattle; dental bonding; drug effect; enamel; Acetone; Animals; Cattle; Dental Bonding; Dental Cements; Dental Enamel; Dentifrices; Polymethacrylic Acids; Tooth Bleaching Agents